2013
DOI: 10.1007/s00775-013-1076-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of EGFR/HER2 cancer biomarkers by protein MRI contrast agents

Abstract: Epidermal growth factor receptor (EGFR) and HER2 are major prognosis biomarkers and drug targets overexpressed in various types of cancer cells. There is a pressing need to develop MRI contrast agents capable of enhancing the contrast between normal tissues and tumors with high relaxivity, capable of targeting tumors, and with high intratumoral distribution and minimal toxicity. In this review, we first discuss EGFR signaling and its role in tumor progression as a major drug target. We then report our progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 150 publications
(134 reference statements)
0
27
0
Order By: Relevance
“…As for every in vivo application, biological barriers like the blood-brain-barrier and toxicity of the contrast agent also need to be considered. Three different approaches for targeted delivery are highlighted in this issue: Yang proposes protein-based biomarkers targeting liver tumors [49]; Sherry and Mason report a small gadolinium complex that naturally accumulates in hypoxic tumors [50]; and Tóth and coworkers use targeting moieties for imaging β-amyloid plaques [51]. …”
Section: Targeted Deliverymentioning
confidence: 99%
“…As for every in vivo application, biological barriers like the blood-brain-barrier and toxicity of the contrast agent also need to be considered. Three different approaches for targeted delivery are highlighted in this issue: Yang proposes protein-based biomarkers targeting liver tumors [49]; Sherry and Mason report a small gadolinium complex that naturally accumulates in hypoxic tumors [50]; and Tóth and coworkers use targeting moieties for imaging β-amyloid plaques [51]. …”
Section: Targeted Deliverymentioning
confidence: 99%
“…19,26,33,61,62 Our current studies illuminate several additional advances in molecular imaging especially for prostate cancer. First, GRPR and HER-2 are expressed in multiple tumors, therefore, these GRPR and HER-2 targeted contrast agents can be applied for the imaging of tumor originating from different tissues.…”
Section: Discussionmentioning
confidence: 78%
“…These studies along with our previous studies further demonstrate the strategy of extending the protein contrast agent to biomarker targeting by the addition of peptide, glycans, or synthesized small ligands without sacrificing metal binding affinity and relaxivity. 1921,30 …”
Section: Discussionmentioning
confidence: 99%
“…Yang et al have reported on the development of novel type of Gd 3+ -binding protein MRI probes, ProCA [3,44,45]. The scaffold of these CAs is based on the domain 1 of CD2.…”
Section: Epidermal Growth Factor Receptor/her2 (Egfr/her2)mentioning
confidence: 99%